1991
DOI: 10.2151/jmsj1965.69.1_127
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Simulation of Airflow and Orographic Rain over the Island of Hawaii

Abstract: A three-dimensional mesoscale numerical model is presented, designed with the capability of simulating the airflow and orographically-induced rain in the presence of steep irregular terrain. The model utilizes a fourth-order accurate version of Arakawa's potential enstrophy and total energy conserving scheme to improve the simulation of nonlinear aspects of the airflow over steep topography, along with an adiabatic reference atmosphere to reduce the effects of orographic truncation errors. The precipitation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…However, it has been found that other factors such as changes in upstream wind, boundary layer frictions, complexity of terrains, Coriolis force, and diurnal heating could also change the final appearance of the vortices/wakes [e.g., Reisner and Smolarkiewicz , 1994]. Due to the limited computing resources, the above effects were studied separately with limited domain sizes and short integration periods (12–24 hours) [e.g., Ueyoshi and Han , 1991].…”
Section: The Numerical Resultsmentioning
confidence: 99%
“…However, it has been found that other factors such as changes in upstream wind, boundary layer frictions, complexity of terrains, Coriolis force, and diurnal heating could also change the final appearance of the vortices/wakes [e.g., Reisner and Smolarkiewicz , 1994]. Due to the limited computing resources, the above effects were studied separately with limited domain sizes and short integration periods (12–24 hours) [e.g., Ueyoshi and Han , 1991].…”
Section: The Numerical Resultsmentioning
confidence: 99%
“…Numerical simulations of Hawaii's wake by Smolarkiewicz et al (1988) and Ueyoshi and Han (1991) both predict shedding eddies behind Hawaii. In the latter simulation, the Froude number upstream of Hawaii, calculated from the composite wind and temperature profiles fixed in time and space, was Fr<0.4.…”
Section: Discussionmentioning
confidence: 98%
“…It is suggested that the above discrepancy between observations and simulations may be due to the simplified topography included in the models. One problem with the simulation by Ueyoshi and Han (1991) is that the island of Maui was not included in the model topography, which would have further accelerated the trade wind moving through Alenuihaha Channel between Maui and Hawaii. We speculate that this exclusion of Maui may have had a significant influence on simulated vortex shedding behind Hawaii because the accelerated northeasterly trade wind through the Channel might have deterred vortex shedding in a mechanism similar to that in the Maui Vortex case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, many numerical studies for the island of Hawaii have been conducted (Nickerson 1979;Fett and Bury, 1981;Smolarkiewicz et al 1988;Rasmussen et al 1989;Ueyoshi and Han 1991;Reisner and Smolarkiewicz 1994;and others); however, the diurnal thermal forcing from the land surface was crudely estimated in these studies. Feng and Chen (2001) used the fifth-generation Pennsylvania State University-National Center for Atmospheric Research (NCAR) Mesoscale Model (MM5), version 1, to successfully simulate the nocturnal regime on the windward side of the island of Hawaii with the land surface specified as tropical rain forest over the entire island.…”
Section: Introductionmentioning
confidence: 99%